Testing of steel plate shear walls with composite columns and infill plates connected to beams only. (1st April 2017) - Guo, Lanhui; Rong, Qin; Qu, Bing; Liu, Jiepeng
Highlights: Buckling restrained plates offer higher strengths than conventional plates. Buckling restrained plates are less ductile than conventional plates. Buckling restrained plates have more favorable energy absorption features. Plate edge boundary conditions affect system strength. Abstract: This paper focuses on a new type of Steel Plate Shear Walls (SPSWs) consisting of Concrete Filled Steel Tube (CFST) columns and infill plates connected to beams only. To evaluate seismic behavior of such a SPSW system, this research team conducted an experimental investigation on three two-story specimens. The specimens were varied to compare performances of the systems consisting of conventional infill plates permitting buckling and infill plates restrained by reinforced concrete panels for prevention of plate buckling. Test results revealed that a system with buckling restrained infill plates tends to have a higher strength but lower ductility than the one having conventional infill plates with similar geometries and material properties. Moreover, hysteretic energy dissipation feature remains the same in the specimens with buckling restrained infill plates regardless of infill plate dimensions and plate edge boundary conditions. Overall, the new SPSWs with conventional infill plates and buckling restrained infill plates both exhibited stable hysteretic responses and acceptable ductility under cyclic loading; hence, they are recommended for future practice.